A Short Note on the Propagation of Cryptomeria Japonica and Casuarina Equisitlfolia by Branch Cutting - Darral, S. N. (Indian Forester, 1948)
the note with his illustrations describes the possibility of propagation Cryptomeria japonica and Casuarina equisitifblia from their branch cuttings. Indications are that Cryptomeria can cut roots ever without application of any harmones